Environmental and Socio-economic Impact Assessment in Hazaribag Area of Dhaka for Tannery Relocation - Iqbal, Ashik; Hasan, Md. Hasibul; Rasheduzzman, M.; Paul, Shuva Ranjan; Hamid, Rubaiya (Innovation Journal of Social Sciences and Economic Review, 2023)
The study aims to assess the impact of tannery relocation on the environment, social and economic conditions, livelihood, and the perceptions of institutions and stakeholders in the Hazaribag area. This research seeks to understand both the positive and negative effects of relocation, particularly in terms of environmental improvement and socio-economic challenges. The study employs a mixed-method approach, including a field survey and Participatory Rural Appraisal (PRA) tools such as Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs). This framework is designed to gather qualitative data from a wide range of stakeholders, providing a comprehensive understanding of the post-relocation scenario. The findings indicate that the relocation has led to significant improvements in the surrounding environment, including better air quality, reduced Odor, and enhanced surface water conditions. However, the relocation has also resulted in substantial socio-economic challenges. Many tannery workers have become unemployed or have been forced to take jobs outside their areas of expertise, leading to a decline in the local economy. Additionally, conflicts have emerged between tannery owners and workers. The government’s management of the post-relocation situation in the brownfield has been inadequate. The study concludes that while tannery relocation has had a positive environmental impact, it has also created significant socio-economic issues that need to be addressed. The current management of the post-relocation scenario is insufficient, particularly in addressing the socio-economic needs of the affected population.
Keywords: Hazaribagh; Tannery Industry; Relocation; Impact Assessment; Environmental Impact; Socio-Economic Impact